The Geomagnetic Field Affect the Manifestation of Activity of Synthetic Biologically Active Substances. - Zhigacheva, Irina Valentinovna; Vladimir, Binyukov; Elena, Mil; Saidgarey, Fattahov; Aleksandr, Konovalov (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
We compared the influence of aqueous solutions of plant growth regulator (PGR) melaphen (MF), made under normal conditions and in conditions of low level electromagnetic field of the Earth (in permalloy container) on the functional state of 6-day-old pea seedlings mitochondria In a concentration range from 2—10-5 to 2—10-9M melaphen that were cooked in various ways, had the same effects to the maximum rates of oxidation of NAD-dependent substrates and the fluorescence intensity of peroxidation products which were caused by the "aging" of mitochondria. However, in the concentration range of 2—10-10 M and below MF solutions,which were prepared in normal conditions and in conditions of low intensity of electromagnetic fields have a different impact on the rates of oxidation of NAD-dependent substrates and the fluorescence intensity of lipid peroxidation products. It can be assumed that the biological effects of the drug are associated with the formation of a nanoassociates for the occurrence of which requires the presence of electromagnetic fields. However,after the processing of pea seeds 2—10-12 M melaphene prepared in various ways ,observed identical protective effect for pea seedlings that are in conditions of insufficient watering and moderate cooling. It is assumed that the processing of seeds outside of the container (on the table) leads to the formation of nanoassociates.